Immune exclusion-Wnt/CTNNB1 class predicts resistance to immunotherapies in HCC - Pinyol, Roser (Clin Cancer Res, 2019)
Next generation sequencing has provided information on actionable targets and biomarkers of response in oncology. In HCC, Wnt/CTNNB1 mutations characterize the immune excluded class (cold tumors) and might represent the biomarkers predicting resistance to immune checkpoint inhibitors. Large-scale validation of this data is needed to customize immunotherapy in advanced HCC.